The rack - Hull, M. (1998)
About the rack - a device using static, active stretching principles to achieve increased plantar flexion (increased range of ankle motion) by stretching structures (muscles, tendons and ligaments) in the ankle and in the anterior aspect of the lower leg. In effect, it is a large piece of plastic with a two inch wide nylon strap. It is for flexibility training for swimmers, triathletes, runnners and others to develop flexibility.